2023
DOI: 10.1186/s12979-023-00344-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin virus-like particles incorporated with membrane-bound cytokine adjuvants provide protection against homologous and heterologous influenza virus challenge in aged mice

Abstract: Background Current influenza vaccines deliver satisfactory results in young people but are less effective in the elderly. Development of vaccines for an ever-increasing aging population has been an arduous challenge due to immunosenescence that impairs the immune response in the aged, both quantitatively and qualitatively. Results To potentially enhance vaccine efficacy in the elderly, we investigated the immunogenicity and cross-protection of infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
(71 reference statements)
0
4
0
Order By: Relevance
“… 34 VLPs are generated by expressing viral proteins derived from structural proteins. 58 , 59 When expressed, a phenomenon occurs where viral proteins fold and form an outer structure of a virus. 58 , 59 From there, viral antigens, like HA and NA proteins, can be expressed and bound to the surface of the viral architecture.…”
Section: Novel Technologies and Upcoming Influenza Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“… 34 VLPs are generated by expressing viral proteins derived from structural proteins. 58 , 59 When expressed, a phenomenon occurs where viral proteins fold and form an outer structure of a virus. 58 , 59 From there, viral antigens, like HA and NA proteins, can be expressed and bound to the surface of the viral architecture.…”
Section: Novel Technologies and Upcoming Influenza Vaccinesmentioning
confidence: 99%
“… 58 , 59 When expressed, a phenomenon occurs where viral proteins fold and form an outer structure of a virus. 58 , 59 From there, viral antigens, like HA and NA proteins, can be expressed and bound to the surface of the viral architecture. 58 , 59 , 60 An advantage of VLP is that they do not contain viral genetic material, which makes them relatively safe as they cannot undergo viral replication.…”
Section: Novel Technologies and Upcoming Influenza Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that Flu VLP might have acted as an adjuvant before infection resulting in a better bystander effect upon challenge with the SARS-CoV-2. We have recently shown that Flu VLP induces a cross-protective effect against heterologous influenza viruses without inducing hemagglutination inhibiting antibody response (50). Therefore, further studies are needed to understand the potential cross-protection between influenza and SARS-CoV-2 and the associated mechanisms.…”
Section: Sars-cov-2 and Influenza Co-infection Is A Global Concern Be...mentioning
confidence: 99%